Defect-engineered reduced graphene oxide sheets with high electric conductivity and controlled thermal conductivity for soft and flexible wearable thermoelectric generators. (December 2018) - Zeng, Wei; Tao, Xiao-Ming; Lin, Shuping; Lee, Ching; Shi, Dongliang; Lam, Kwok-ho; Huang, Baoling; Wang, Qiaoming; Zhao, Yue
Abstract: The direct use of graphene for potential thermoelectric material requires the opening of its bandgap without loss of its high electric conductivity. We herein demonstrate a synchronous reduction and assembly strategy to fabricate large-area reduced graphene oxide films with high electric conductivity and optimized low thermal conductivity assembly. The reduced graphene oxide films have a high electric conductivity and low thermal conductivity, which results from high longitudinal carrier mobility of the lattice domains as well as the enhanced scattering of phonons in the defects and their boundary that substantially reduces the mean phonon free path and the thermal conductivity. Flexible thermoelectric generators were prepared by assembling reduced graphene oxide film on 3D printed polydimethylsiloxane grids, demonstrating a remarkable output voltage of 57.33 mV/g at a temperature difference of 50 K. A wristband-type flexible thermoelectric generator with 7 repeating units generated a maximum power density of 4.19 µW/g at ambient temperature of 15 °C. The 3D printed generator is promising in providing power autonomy to wearable microwatt electronic devices. In addition, we believe that this work can be easily scaled up and can offer the pathway to produce large-scale manufacturing of graphene based materials for future microelectronics and large-scaled flexible and wearable energy harvesting systems. Graphical abstract: Highlights: A synchronous reduction and assembly strategy to fabricate large-area rGO films on three-dimensional surfaces. The rGO films have a high electric conductivity and low thermal conductivity as well as an opened bandgap. Flexible TE generators demonstrated by assembling rGO film on 3D printed PDMS grids with good TE performance.